Roles of matrix metalloproteinases in flow-induced outward vascular remodeling - Ota, Ryo (2009)
Sustained hemodynamic stresses, especially high blood flow, result in flow-induced outward vascular remodeling. Our previous study showed that macrophage depletion reduced flow-induced outward remodeling of the rat common carotid artery, indicating that macrophages play critical roles in flow-induced outward vascular remodeling. Macrophage is known to release proteinases, including matrix metalloproteinases (MMPs). Degradation and loosening of extracellular matrix by MMPs may facilitate vascular remodeling. Therefore, we assessed the roles of MMPs in flow-induced outward vascular remodeling by using the flow-augmented common carotid artery model in mice. We validated that ligation of the left common carotid artery increased blood flow and luminal diameter of the right common carotid artery without significant change in blood pressure of mice. To assess the roles of MMPs in flow-induced outward vascular remodeling, we used doxycycline (broad-spectrum MMP inhibitor), SB-3CT (selective MMP inhibitor), MMP-9 knockout mice, and MMP-12 knockout mice. Although there was only a trend for doxycycline treatment to reduce flow-induced outward vascular remodeling, SB-3CT treatment significantly reduced flow-induced outward vascular remodeling. In addition, flow-induced outward vascular remodeling was significantly reduced in MMP-9 knockout mice, but not in MMP-12 knockout mice. These data revealed that MMPs, especially MMP-9, play critical roles in flow-induced outward vascular remodeling.